2015
DOI: 10.2131/jts.40.615
|View full text |Cite
|
Sign up to set email alerts
|

Sirt 1 activator inhibits the AGE-induced apoptosis and p53 acetylation in human vascular endothelial cells

Abstract: -Advanced glycation end products (AGEs) by nonenzymatic glycation reactions are extremely accumulated in the diabetic vascular cells, neurons, and glia, and are confirmed to play important role in the pathogenesis of diabetes mellitus -induced cardiovascular complications. Sirt 1, known as mammalian sirtuin, has been recognized to regulate insulin secretion and protect cells against oxidative stress, which is promoted by the accumulated AGEs in cardiovascular cells. In the present study, we treated human endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…AGE-BSA is not a strong apoptosis inducer. For studing apoptosis, the AGE-BSA dose often ranges between 100 and 300 μg/ml, and the treatment time is 24 or 48 h3940. The level of AGE-BSA-induced apoptosis is dose- and time-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…AGE-BSA is not a strong apoptosis inducer. For studing apoptosis, the AGE-BSA dose often ranges between 100 and 300 μg/ml, and the treatment time is 24 or 48 h3940. The level of AGE-BSA-induced apoptosis is dose- and time-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Because p53 is deacetylated by SIRT1 the Acp53/p53 ratio was used to assess the activity of SIRT1 (Chung et al 2015;Feng et al 2015;Kim et al 2016;Li et al 2015;Song et al 2015;Weidele et al 2017) and the results showed that exercise and NAM treatment as well as the combined effects of these increased the activity of SIRT1 in old muscle. In terms of exercise training this is similar to our earlier results (Koltai et al 2010(Koltai et al , 2012 however, the intensity of training was much less than that used in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 expression increases in the conditions of H 2 O 2 -induced oxidative stress, and sirtuin activation inhibits p53-dependent apoptosis [240]. Down-regulation of SIRT1's influence on p53 mediates responses to several stressors in other cell types [204,224] and to a range of age/hyperglycaemia-related vascular endothelial pathologies [107,233]. Similar mechanisms of age-related, glucose-elicited damage might also be involved in neurodegenerative disorders along with generalized oxidative/nitrosative stress.…”
Section: Transcriptional and Post-transcriptional Regulators As Sirtumentioning
confidence: 99%